Polymers Enhancing Bioavailability in Drug Delivery - Ana I. Fernandes; Angela F. Jozala (MDPI AG, 2022)
A drug's bioavailability, i.e., the extent to and rate at which it enters the systemic circulation, thus accessing the site of action, is largely determined by the properties of the drug [...]